Effect of Light Intensity on the Total Flavonoid and Total Phenolic Contents of Mikania Micrantha and Tridax Procumbens - Idris, Aisha; C. Linatoc, Alona; Mustapha Muhammad, Surayya; Muhammad Aliyu, Aisha; Abu Bakar, Mohd Fadzelly (Journal of Science and Technology, 2018)
Flavonoid and phenolics are secondary metabolites produced by plants in response to harsh environmental conditions. Light is one of the most important factor that affects their production. Mikania micrantha and Tridax procumbens are plants belonging to Asteraceae family, and they have bioactivity due to their flavonoid and phenolic contents. The objective of the research is to determine the effect of varying light intensities on the total flavonoid and total phenolic contents of M. micrantha and T. procumbens using three solvents (ethanol, methanol and water). Total flavonoid contents was determined based on the aluminium chloride colorimetry method while total phenolic contents was determined based on the folin-chiocalteau reagent. The results obtained in the study shows that ethanol recovers more flavonoid and phenolic than the other solvents (P < 0.05). Besides, T. procumbens had more flavonoid and phenolic content compared to M. micrantha (P < 0.05). Nevertheless, the flavonoid and phenolic contents recovered from sun exposed plants was more than that recovered from shaded plants (P < 0.05). This leads to a conclusion that high light intensity can increase the concentration of flavonoid and phenolic of M. micrantha and T. procumbens.